2022
DOI: 10.1111/jdv.17907
|View full text |Cite
|
Sign up to set email alerts
|

Segmental facial infantile haemangiomas in the era of propranolol: evaluation at 6 years of age

Abstract: Background The long‐term evolution of children with segmental facial infantile haemangioma (SFIH) treated with propranolol remains unstudied. Objectives The objective of this study was to evaluate the neurodevelopmental features of children with SFIH treated with propranolol at 6 years of age. Methods This retrospective case series study was conducted from January 2008 to June 2020 using data from medical files, patient examinations and appointments spanning 6 years. To be included, patients should present SFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Bradycardia is more rarely observed, and asymptomatic hypotension and diarrhea are sometimes present at the start of treatment. Propranolol is also the first‐line medical treatment for PHACE syndrome, 13 as short‐ and long‐term safety data have been found to be reasonable 10,13 …”
Section: Medical Therapies With Antiangiogenic Demonstrated Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…Bradycardia is more rarely observed, and asymptomatic hypotension and diarrhea are sometimes present at the start of treatment. Propranolol is also the first‐line medical treatment for PHACE syndrome, 13 as short‐ and long‐term safety data have been found to be reasonable 10,13 …”
Section: Medical Therapies With Antiangiogenic Demonstrated Effectmentioning
confidence: 99%
“…A recent study on large facial IHs showed that the median length of propranolol treatment was 16 months with a median age at treatment cessation of 21 months, and this was extended to 25 months if the V3 segment was involved (i.e., location in the beard area). 10 Unlike corticosteroids, resistance to treatment is rare and late treatment of IHs beyond the proliferative phase is also possible. 11 The acceptability and tolerance of propranolol is usually good in infants.…”
Section: Medical Therapies With Antiangiogenic Demonstrated Effect 21...mentioning
confidence: 99%
See 2 more Smart Citations
“…After 25 years, reports of cases of PHACE syndrome have multiplied and the list of associated malformations is getting longer and longer 4 and includes both organs originating from the ectoderm (such as the cerebellum) and endoderm (such as the thyroid) and not only from the mesoderm, which is the embryonic tissue from which the vessels originate.…”
mentioning
confidence: 99%